2017
DOI: 10.1038/leu.2017.222
|View full text |Cite
|
Sign up to set email alerts
|

Concordant bone marrow involvement of diffuse large B-cell lymphoma represents a distinct clinical and biological entity in the era of immunotherapy

Abstract: In diffuse large B-cell lymphoma (DLBCL), the clinical and biological significance of concordant and discordant bone marrow (BM) involvement have not been well investigated. We evaluated 712 de novo DLBCL patients with front-line rituximab-containing treatment, including 263 patients with positive and 449 with negative BM status. Compared with negative BM disease, concordant BM adversely impacted overall and progression-free survival, probably independent of the International Prognostic Index (IPI) and cell-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 47 publications
2
43
0
1
Order By: Relevance
“…In our series of 189 patients treated with R-CHOP-like, we observed that high-grade BM involvement had a significantly unfavorable effect on PFS, independent of R-IPI, even considering only stage IV patients. This finding is in accordance with the results reported by Sehn et al [2] from larger series and, in agreement with these observations, a recent study published by Yao et al [18] has suggested that patients with DLBCL and concordant BM involvement should be considered a distinct entity due to a more aggressive course and poor prognosis in terms of both PFS and OS. However, in our series, concordant involvement had no independent prognostic influence on OS in the multivariate analysis, probably due to the small number of patients with concordant infiltration and to the relatively high efficacy of the salvage therapies employed, including autologous and allogeneic stem cell transplantation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our series of 189 patients treated with R-CHOP-like, we observed that high-grade BM involvement had a significantly unfavorable effect on PFS, independent of R-IPI, even considering only stage IV patients. This finding is in accordance with the results reported by Sehn et al [2] from larger series and, in agreement with these observations, a recent study published by Yao et al [18] has suggested that patients with DLBCL and concordant BM involvement should be considered a distinct entity due to a more aggressive course and poor prognosis in terms of both PFS and OS. However, in our series, concordant involvement had no independent prognostic influence on OS in the multivariate analysis, probably due to the small number of patients with concordant infiltration and to the relatively high efficacy of the salvage therapies employed, including autologous and allogeneic stem cell transplantation.…”
Section: Discussionsupporting
confidence: 93%
“…In both studies, the number of events was small and the multivariate analysis was limited to the IPI or CNS-IPI score, so larger studies are needed to confirm these results. In the recent and previously mentioned analysis from Yao et al [18], investigators do not describe a higher incidence of CNS relapse in patients with concordant BM infiltration. However, CNS prophylaxis, including systemic high dose methotrexate (MTX) and cytarabine or intrathecal MTX, were administered to 61.8% of patients.…”
Section: Discussionmentioning
confidence: 88%
“…Concordant bone marrow involvement of DLBCL disease is a risk factor for short OS, but not for discordant bone marrow involvement of DLBCL disease. The OS period for patients with discordant bone marrow involvement is comparable to those without bone marrow involvement of disease 32,33 . In this study, only patients with concordant bone marrow involvement of disease was categorised in positive bone marrow group.…”
Section: Discussionmentioning
confidence: 92%
“…Literatürde kemik iliği tutulum sıklığı, yaklaşık %10-20 olarak bildirilmiş olup, çalışmamız %11,6 oranı ile benzerdi. Kemik iliği tutulumu, genel sağkalımın daha kötü olacağını öngörmektedir (16,17) .…”
Section: Discussionunclassified